2006
DOI: 10.1164/rccm.200510-1634oc
|View full text |Cite
|
Sign up to set email alerts
|

Regional Pulmonary Perfusion, Inflation, and Ventilation Defects in Bronchoconstricted Patients with Asthma

Abstract: Rationale: Bronchoconstriction in asthma leads to heterogeneous ventilation and the formation of large and contiguous ventilation defects in the lungs. However, the regional adaptations of pulmonary perfusion (Q ) to such ventilation defects have not been well studied. Methods: We used positron emission tomography to assess the intrapulmonary kinetics of intravenously infused tracer nitrogen-13 ( 13 NN), and measured the regional distributions of ventilation and perfusion in 11 patients with mild asthma. For e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
105
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 39 publications
16
105
0
Order By: Relevance
“…This region was also the dependent part of the lung because the animals were studied supine, which raises the possibility that gravity could have played a role in our observations. Certainly, humans with asthma during bronchoconstriction exhibit poorer ventilation in dependent lung regions (10,11). On the other hand, it is perhaps doubtful that gravity could have a significant effect in a lung as small as that of the mouse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This region was also the dependent part of the lung because the animals were studied supine, which raises the possibility that gravity could have played a role in our observations. Certainly, humans with asthma during bronchoconstriction exhibit poorer ventilation in dependent lung regions (10,11). On the other hand, it is perhaps doubtful that gravity could have a significant effect in a lung as small as that of the mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Single-photon emission CT with inhaled Technegas has shown that, even though airway closure appears to be a normal feature in a healthy lung, the pattern by which closure occurs is altered in subjects with asthma (11). It has also recently been shown that humans with asthma challenged with methacholine have clusters of underventilated alveoli adjacent to normally ventilated areas, and that this pattern can be understood in terms of self-organized clusters of small airway closures (10). Similarly, a correlation has been reported between the amount of air trapped in the lungs and the reversibility of small airway constriction (25), again suggesting that it is the small airways that close during bronchoconstriction in human lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Washout was poor in areas of low perfusion. Because of perfusion redistribution, the V/Q mismatch was reduced (Harris et al, 2006). Compared with healthy volunteers, perfusion heterogeneity was also greater in patients with mild to moderate COPD, as was the heterogeneity in V/Q, which was primarily caused by the heterogeneity in perfusion and not so much in ventilation (Vidal Melo et al, 2010).…”
Section: Imaging In Respiratory Diseases: From Animal Models To Patientsmentioning
confidence: 98%
“…Regional patterns of ventilation in asthma have also been explored using inhaled gas contrast agents in conjunction with imaging (11)(12)(13)(14), including hyperpolarized helium-3 magnetic resonance imaging (HP MRI) (15). Like MDCT measures of parenchymal density, whole lung measures of ventilatory defect number on HP MRI correlate with obstructive physiology (7,14,16).…”
Section: Introductionmentioning
confidence: 99%